The Relationship Between Tuberculosis Knowledge and The Attitudes and Behaviors Of Dayah Students - Rahman, Muhammad; Kurniawan, Ferry Dwi; Habibie, Yopie Afriandi; Arliny, Yunita; Maulina, Novi (Journal of International Surgery and Clinical Medicine, 2024)
Introduction: Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis and is one of the leading causes of death worldwide. Indonesia ranks second in global TB case counts, with a high transmission rate, particularly in high-risk environments such as Islamic boarding schools. This study aims to evaluate the knowledge, attitudes, and behaviors related to TB among students at Dayah Madrasah Aliyah Swasta Babun Najah in Banda Aceh. Additionally, it will analyze the relationship between their knowledge, attitudes, and behaviors in the context of TB prevention. Methods: This study employed an observational analytic method with a cross-sectional design and utilized cluster sampling. Primary data were gathered through questionnaires. The research was conducted at Dayah Madrasah Aliyah Swasta Babun Najah, located in the Ulee Kareng District of Banda Aceh, on August 29, 2024. Bivariate analysis was performed using the non-parametric Spearman's rank correlation coefficient test. Results: A total of 90 students participated in the study. The findings revealed that 67.8% of respondents had good knowledge, 78.9% demonstrated positive attitudes, and 47.8% exhibited good behaviors regarding tuberculosis (TB) prevention. Spearman Rank analysis indicated a moderately strong positive correlation between knowledge and attitudes (r = 0.527) and between knowledge and behaviors (r = 0.535), with a p-value of less than 0.025. Conclusion: Enhancing knowledge among students is crucial for fostering better attitudes and behaviors related to TB prevention, particularly in high-risk environments.